Assessing Human Health Risks in Asejire Lake: Implications for Water Resources in Industrialized Ibadan, Nigeria - Omotoso, Oladele Ajiboro; Ojo, Olusola Johnson; Matimoju, Oluwatobi; Farinu, Olabisi Hamidah; Adeboye, Ayodele Christiana; Adeniran, Yetunde Oloyede (Journal of Sustainable Natural Resources, 2023)
The preliminary human health risk assessment of Asejire Lake water, Ibadan, Southwestern Nigeria has been carried out. The industrialized Ibadan environs is thickly populated and this really has influence on the water resources in the area. Some selected toxic metals analyzed were subjected to evaluation using contamination indexes, carcinogenic and non-carcinogenic health risk parameters and also compared with WHO and NSDWQ (Nigerian Standard for Drinking Water Quality) water quality standards. ICP-MS laboratory techniques were used for hydro-chemical analyses to give the concentrations of the selected metals. Average concentrations of the metals are less than prescribed standards except Al (0.39 ppm) and Fe (1.41 ppm). The contamination factors ranged from low contamination to very extremely high contamination factors with extremely high degree of contamination. Non-carcinogenic parameters values are generally